Cyclosporine before Coronary Artery Bypass Grafting Does Not Prevent Postoperative Decreases in Renal Function: A Randomized Clinical Trial. (April 2018) - Ederoth, Per; Dardashti, Alain; Grins, Edgars; Brondén, Björn; Metzsch, Carsten; Erdling, André; Nozohoor, Shahab; Mokhtari, Arash; Hansson, Magnus J.; Elmér, Eskil; Algotsson, Lars; Jovinge, Stefan; et al.
Abstract : Background: Acute kidney injury is a common complication after cardiac surgery, leading to increased morbidity and mortality. One suggested cause for acute kidney injury is extracorporeal circulation–induced ischemia–reperfusion injury. In animal studies, cyclosporine has been shown to reduce ischemia–reperfusion injury in the kidneys. We hypothesized that administering cyclosporine before extracorporeal circulation could protect the kidneys in patients undergoing cardiac surgery. Methods: The Cyclosporine to Protect Renal Function in Cardiac Surgery (CiPRICS) study was an investigator-initiated, double-blind, randomized, placebo-controlled, single-center study. The primary objective was to assess if cyclosporine could reduce acute kidney injury in patients undergoing coronary artery bypass grafting surgery with extracorporeal circulation. In the study, 154 patients with an estimated glomerular filtration rate of 15 to 90 ml · min –1 · 1.73 m –2 were enrolled. Study patients were randomized to receive 2.5 mg/kg cyclosporine or placebo intravenously before surgery. The primary endpoint was relative plasma cystatin C changes from the preoperative day to postoperative day 3. Secondary endpoints included biomarkers of kidney, heart, and brain injury. Results: All enrolled patients were analyzed. The cyclosporine group (136.4 ± 35.6%) showed a more pronounced increase from baseline plasma cystatin C to day 3 compared to placebo (115.9 ± 30.8%), difference, 20.6% (95% CI, 10.2 to 31.2%, P < 0.001). The same pattern was observed for the other renal markers. The cyclosporine group had more patients in Risk Injury Failure Loss End-stage (RIFLE) groups R (risk), I (injury), or F (failure; 31% vs. 8%, P < 0.001). There were no differences in safety parameter distribution between groups. Conclusions: Administration of cyclosporine did not protect coronary artery bypass grafting patients from acute kidney injury. Instead, cyclosporine caused a decrease in renal function compared to placebo that resolved after 1 month. Abstract : In a double-blind trial, 154 cardiac surgical patients were randomly assigned to 2.5 mg/kg cyclosporine or placebo. Plasma cystatin C, a marker of renal injury, increased more in patients given cyclosporine. Cyclosporine does not reduce the risk of acute renal injury after cardiac surgery.Supplemental Digital Content is available in the text.